pH-Activatable Charge-Reversal Polymer-Based Nanocarriers for Targeted Delivery of Antihepatoma Compound - Chen, Shuai (Langmuir : the ACS journal of surfaces and colloids, 2023)
Chemotherapy is one of the available cancer treatments which has been successfully employed to prolong the survival of cancer patients. However, it remains a major challenge to develop effective chemotherapeutic agents by reducing off-target toxicity, improving bioavailability, and effectively prolonging blood circulation. The pH profile of tumor cells is abnormal to that of normal cells, making it a potential breakthrough for designing effective chemotherapeutic drug agents. Here, the pH-activatable charge-reversal supramolecular nanocarriers, named MI7-β-CD/SA NPs, were prepared through a simple and "green" constructive process. MI7-β-CD/SA NPs possess both pH-induced charge-reversal and disassembly properties that were exploited to investigate the loading, delivery, and pH-responsive controlled release of the antitumor compound celastrol (CSL). CSLMI7-β-CD/SA NPs displayed low hemolysis, good biocompatibility, and targeted uptake. Furthermore, CSL@MI7-β-CD/SA NPs exhibited superior apoptosis rates against SMMC-7721 cell lines compared with CSL, when CSL@MI7-β-CD/SA NPs and CSL were administered at a mass concentration of 5.0 μg/mL, i.e., the CSL content in CSL@MI7-β-CD/SA NPs was relatively lower than that of intact CSL. We expected that MI7-β-CD/SA NPs featuring pH-triggered charge reversal could offer a promising controlled release strategy that would then facilitate the clinical conversion of antitumor drugs